Investigating the strategic behaviors in integrated speaking assessment. (November 2018) - Huang, Heng-Tsung Danny; Hung, Shao-Ting Alan
Abstract: Integrated speaking test tasks (integrated tasks) invite test-takers to integrate the provided reading and listening input into their oral response. This research examined the strategic behaviors associated with such tasks and explored their relationships with test performance. Drawing on two integrated tasks and a custom-developed survey inventory, the researcher collected empirical data from a total of 177 EFL learners in the official study. The conduct of exploratory factor analysis and structural equation modeling revealed that integrated tasks elicited three primary groups of strategic behaviors: discourse synthesis strategy use, cognitive strategy use, and communication strategy use. Moreover, discourse synthesis strategy use impacted performance indirectly, while cognitive and communication strategy use both directly affected performance, with the former exerting a positive effect and the latter a negative influence. These findings substantiated the L2 theoretical frameworks that incorporate strategic competence as a critical component, confirmed integrated assessment as tapping into a unique construct, offered validity evidence for integrated speaking assessment, and endorsed the implementation of strategy training sessions in L2 classes.